Effect of cadmium chloride on metallothionein levels in carp - Kovarova, Jana; Kizek, Rene; Adam, Vojtech; Harustiakova, Danka; Celechovska, Olga; Svobodova, Zdenka (Sensors (Basel, Switzerland), 2009)
Due to anthropogenic activities, heavy metals still represent a threat for various trophic levels. If aquatic animals are exposed to heavy metals, we can obviously observe considerable toxicity. It is well known that organisms treated with heavy metals synthesize low molecular mass compounds rich in cysteine. In this work the effects of cadmium chloride (2.5, 5, 7.5, 10 and 12.5 mg/L) on common carp (Cyprinus carpio) was investigated. We determined cadmium content in tissue of muscle, liver and kidney by atomic absorption spectrometry with electrothermal atomization and content of metallothionein (MT) in the same tissues by the Brdicka reaction. Electrochemical methods can be considered as suitable and sensitive tools for MT determination in carp tissues. Results of our study showed a gradually enhancing of cadmium content in muscle with time and dose of cadmium chloride in water. MT levels in liver reached both high levels (above 130 ng/g) in fish exposed to 2.5, 5 and 7.5 mg/L and low level (to 50 ng/g) in fish exposed to 10 and 12.5 mg/L of cadmium chloride. This finding confirms that the synthesis of metallothioneins and binding capacity of these proteins is restricted.
Keywords: bioaccumulation; Cyprinus carpio; heavy metals